Turkey Economic Monitor, August 2020 : Adjusting the Sails - World Bank (World Bank, Washington, DC, 2020)
Despite an initial surge in COVID-19 cases, cross country data suggests that Turkey containedrelatively quickly the spread and worst health effects of the virus. As in other countries, however, continued vigilance is essential to sustain this fragile trend. Turkey’s pandemic response may offer some lessons, notwithstanding country specific conditions. Turkey implemented social distancing, mobility restrictions and health policies relatively quickly. This may have enabled more targeted measures compared to countries that reacted later, forcing them into more widespread lockdowns. Targeted measures in turn could have helped contain the spread of the virus, mortality rates, and perhaps even some of the decline in economic activity. Lessons from other countries suggest that health, social distancing and some mobility measures should be maintained to prevent the risks of a second wave. The economic impact of the COVID-19 health crisis has understandably derailed a fragile economic recovery in Turkey. By the second half of 2019, the economy started to gradually recover from the shock of the mid-2018 economic turmoil. Inflation moderated and external balances narrowed. The situation turned quickly by March 2020 – the TEM takes stock of the economic impact of COVID-19 through five different channels.